Roughage sources for Holstein cows under experimental feeding conditions in Brazil - a meta-analysis - Alessio, Dileta Regina Moro (2018)
The aim of this study was to evaluate the composition, voluntary intake, and digestibility of the diet of Holstein cows, as well as milk yield and milk composition as a function of different roughage sources used under experimental feeding conditions in Brazil, through meta-analysis. The database of this study consisted of 109 experiments with 424 treatments of 3,903 lactating Holstein cows. The data were obtained from studies published between January 2000 and December 2015, and were evaluated by variance analysis. Lactating dairy cow diets with a single source of roughage other than corn silage resulted in lower voluntary intake, milk yield, and differences in milk composition, compared to diets based on corn silage or the combination of two roughages, probably due to reduced nutrient digestibility. Diets based on corn silage are distinguished by feed efficiency, milk yield, and composition. Diets based on the combination of two roughage sources are similar with respect to milk yield and composition, compared to diets based on corn silage; whereas, diets with a single source of roughage (other than corn silage), even when containing a higher proportion of concentrate, led to reduced voluntary intake, milk yield, and food efficiency due to the lower utilization of the nutrients. Diets based on corn silage in general allow a higher proportion of roughage in the diet due to energy density.